Politics of culture and the spirit of critique : dialogues - Rockhill, Gabriel; Gómez-Muller, Alfredo; Benhabib, Seyla (New directions in critical theory., 2011)
The idea of ""culture"" has become central to intellectual debates since at least the end of the 1970s, with the reemergence of longstanding cultural issues becoming an indispensible part of moral and political critique. Additionally, the meaning of culture has expanded beyond its earlier, anthropological meaning to include issues of ethnicity, race, religion, gender, and sexual orientation. Whether informing arguments about a ""clash of civilizations"" or underscoring the importance of ""mainstream multiculturalism, "" inflated notions of culture are ubiquitous, and their prevalence has generated new concerns. Criticism extends from the commodification of difference and the reification of identity to the further marginalization of outside voices. Refusing to reject the cultural shift in politics yet wholly aware of its potential dangers, the contributors to this volume propose innovative solutions and topical interventions. Seyla Benhabib conceptualizes culture as a hybrid and polyvocal system of action and signification. Nancy Fraser strives to solve the recognition/redistribution conundrum. Judith Butler deconstructs sexual and gender identities. Cornel West rejects Black Nationalism and racial reasoning in favor of a cultural democracy that unites various struggles for equality, and Axel Honneth details a normative account of social integration in terms of mutual recognition.